ABUSO E DEPENDÊNCIA DE SUBSTÂNCIAS E SUICÍDIO (REMUNOM, 2025)
The co-occurrence of substance abuse/dependence and suicidal behavior represents a significant public health concern, with profound clinical and forensic implications. This article aims to explore the complex relationship between substance use disorders (SUDs) and suicide, examining epidemiological data, shared risk factors, neurobiological mechanisms, and the impact of different classes of substances. The discussion encompasses the challenges in assessing and managing suicide risk in individuals with SUDs, highlighting the need for integrated treatment approaches. Furthermore, it addresses the medico-legal aspects, including the role of substance use in the determination of suicidal intent in equivocal deaths and its relevance in forensic psychiatric evaluations. Drawing upon literature from authors such as Genival Veloso França, Taborda, Kaplan, and contemporary scientific articles, this paper underscores the critical importance of understanding this dual diagnosis for the development of effective prevention strategies, clinical interventions, and informed medico-legal practice. The synergistic effect of SUDs and other psychiatric comorbidities in increasing suicide risk is also considered, emphasizing the necessity of comprehensive assessments and targeted interventions to mitigate fatal outcomes.